Recent security challenges in cloud computing. (October 2018) - Subramanian, Nalini; Jeyaraj, Andrews
Abstract: Cloud computing is an archetype that enables access to a shared pool of computing resources for cloud users in an on-demand or pay-per-use, fashion. Cloud computing offers several benefits to users and organizations, in terms of capital expenditure and savings in operational expenditure. Despite the existence of such benefits, there are some obstacles that place restrictions on the usage of cloud computing. Security is a major issue that is always considered. The lack of this vital feature results in the negative impact of the computing archetype thus resulting in personal, ethical, and financial harm. This paper will focus and explore the security challenges that are faced by cloud entities. These entities include Cloud Service Provider, the Data Owner and Cloud User. Focusing on the crypto-cloud that constitutes of different Communication, Computation, and Service Level Agreement. Studying the causes and effects of various cyber attacks it will provide the necessary upgrades.